Effect of water injection into the intake manifold on combustion and NOx emissions of CHP engine fuelled with natural gas - Awad, Omar Ibraheem; Arruga, H.; Tao, Hai; Scholl, F.; Kettner, Maurice; Klaissle, M.; Rizalman, Mamat (Springer International Publishing, 2019)
The impact of variable water injection by mass on nitrogen oxide emission and performance characteristics of combined heat and power single-cylinder spark ignition engine fuelled by natural gas under constant power was investigated. For each water/fuel ratio, the combustion phasing was varied by adjusting spark timing and mass of fuel injection to maintain the indicated mean efect pressure at 6.35 bar. It was reported that the nitrogen oxide emissions decreased with the same centre of combustion when the amount of injected water increases. The nitrogen oxide emission averagely decreased by 20–25%, depending on combustion phasing with water/fuel ratio 0.3 compared to 0. Furthermore, the centre of combustion between 15 and 19 °CA after top dead centre represents lower nitrogen oxide emissions. It was recorded that the spark timing had to be advanced with water injection to maintain the indicated mean efect pressure at 6.35 bar. Also, the results of the efects of intake manifold water injection system on performance, combustion and emissions at the lowest level of the nitrogen oxides have been presented. The thermal efciency and indicated specifc fuel consumption were improved with water injection at an operation point compared with a reference point. The maximum nitrogen oxide reduction depends on the maximum water injection rate which is limited by intake air characteristics.